Fusarium poae and mycotoxins: potential risk for consumers - Dinolfo, María Inés (2014)
Fusarium head blight is an important disease affecting cereal grains. Fusarium graminearum is the major causal agent of this disease around the world, but some researchers have documented the increased importance of F. poae. Moreover, F. poae presence may be accompanied of its mycotoxins production, being able to produce trichothecenes of type A diacetoxyscirpenol, monoacetoxyscirpenol, scirpentriol, HT-2 toxin, T-2 toxin and neosolaniol, as well as the type B nivalenol and fusarenone-X. Outside the trichotecenes group, F. poae has been reported to produce enniatins, beauvericin and moniliformin. Due to F. poae may be present in cereal grains used for food and processed products, the aims of this review is to recognize the importance of the hazard effects of the F. poae mycotoxins on animal and human consumers by a short description of the methods that allow determining the mycotoxin presence and analyse the different effects caused by the mycotoxin exposure.